Clinical researchEffectiveness comparison of endoscopic methods of non-varicose upper gastrointestinal bleeding treatment - Kujawski, Krzysztof; Stasiak, Magdalena; Stępień, Mariusz; Rysz, Jacek (Archives of Medical Science, 2010)
Introduction: In every case of upper gastrointestinal bleeding suspicion, an endoscopic examination ought to be performed as a matter of urgency. Finding active bleeding, a visible non-bleeding vessel or a lesion with an adherent clot should be followed by application of an available method of endoscopic therapy. The aim of the study was to compare the effectiveness of various endoscopic treatment techniques such as epinephrine injections, coagulation methods and mechanical methods in the treatment of non-varicose upper gastrointestinal bleeding. Material and methods: Sixty cases of non-varicose upper gastrointestinal bleeding were analysed in terms of the effectiveness of the above-mentioned procedures used in monotherapy or in combination therapy comprising epinephrine injections and clips application. The choice of the applied procedure depended on morphological features and location of the bleeding source, the patient’s general condition, as well as technical equipment and manual skills of the endoscopy staff. Results: The study confirmed the effectiveness of endoscopic treatment of non-varicose upper gastrointestinal bleeding applying the above-mentioned methods. In most patients, this treatment enabled traumatic surgical intervention to be avoided; it was required in only 3 (5%) out of 60 patients with confirmed upper gastrointestinal bleeding. With the first endoscopy, haemostasis was achieved in 47 cases (78.3%) and the second endoscopy, performed due to bleeding recurrence, was successful in the remaining 10 cases (16.7%). Conclusions: In non-varicose upper gastrointestinal bleeding, urgent diagnostic and therapeutic endoscopy should be the first-line management. If the lesion that is the source of bleeding is possible to localize, the endoscopic techniques should be applied. Among the endoscopic procedures used in monotherapy, clips appeared to be the most effective, their effectiveness being comparable to combination therapy. In bleeding from extensive lesions, coagulation methods are considered to be the most efficacious.